Genetic variability and evolution of broad bean wilt virus 1: role of recombination, selection and gene flow - Ferriol, Inmaculada; Ferrer, Rosa M.; Luis-Arteaga, Marisol; Guerri, José; Moreno, Pedro; Rubio, Luis (2017)
Analysis of four genomic regions from 37 geographically diverse isolates of broad bean wilt virus 1 (BBWV-1) showed high genetic diversity in comparison to most plant viruses. Comparison of synonymous and nonsynonymous substitutions of the small coat protein gene (SCP) revealed negative selection for most amino acid positions. Phylogenetic analysis of SCP showed that some BBWV-1 isolates from distant geographical areas were genetically close, suggesting long-distance migration. Analysis of genetic differentiation revealed high gene flow between Spanish and Near Eastern subpopulations, which were separated from North-Central and South-Eastern European subpopulations. Finally, putative recombinant and reassortant genomes were also identified.